Alliance of Randomized Trials of Medicine vs Metabolic Surgery in Type 2 Diabetes (ARMMS‐T2D): Study rationale, design, and methods. Issue 7 (16th March 2022) - Simonson, Donald C.; Hu, Bo; Arterburn, David E.; Schauer, Philip R.; Kashyap, Sangeeta R.; Courcoulas, Anita P.; Cummings, David E.; Patti, Mary‐Elizabeth; Gourash, William F.; Vernon, Ashley H.; Jakicic, John M.; Kirwan, John P.
Abstract: Aims: Long‐term data from randomized clinical trials comparing metabolic (bariatric) surgery versus a medical/lifestyle intervention for treatment of patients with obesity/overweight and type 2 diabetes (T2D) are lacking. The Alliance of Randomized Trials of Medicine vs Metabolic Surgery in Type 2 Diabetes (ARMMS‐T2D) is a consortium of four randomized trials designed to compare long‐term efficacy and safety of surgery versus medical/lifestyle therapy on diabetes control and clinical outcomes. Materials and Methods: Patients with T2D and body mass index (BMI) of 27‐45 kg/m 2 who were previously randomized to metabolic surgery (Roux‐en‐Y gastric bypass, adjustable gastric band, or sleeve gastrectomy) versus medical/lifestyle intervention in the STAMPEDE, SLIMM‐T2D, TRIABETES, or CROSSROADS trials have been enrolled in ARMMS‐T2D for observational follow‐up. The primary outcome is change in glycated haemoglobin after a minimum 7 years of follow‐up, with additional analyses to determine rates of diabetes remission and relapse, as well as cardiovascular and renal endpoints. Results: In total, 302 patients (192 surgical, 110 medical/lifestyle) previously randomized in the four parent studies were eligible for participation in the ARMMS‐T2D observational study. Participant demographics were 71% white, 27% African‐American and 68% female. At baseline: age, 50 ± 8 years; BMI, 36.5 ± 3.5 kg/m 2 ; duration of diabetes, 8.8 ± 5.6 years; glycated haemoglobin, 8.6% ± 1.6%; and fasting glucose, 168 ± 64 mg/dl. More than 35% of patients had a BMI <35 kg/m 2 . Conclusions: ARMMS‐T2D will provide the largest body of long‐term, level 1 evidence to inform clinical decision‐making regarding the comparative durability, efficacy and safety of metabolic surgery relative to a medical/lifestyle intervention among patients with T2D, including those with milder class I obesity or mere overweight.